An advanced virtual synchronous generator control technique for frequency regulation of grid-connected PV system - Ur Rehman, Haseeb; Yan, Xiangwu; Abdelbaky, Mohamed Abdelkarim; Ullah Jan, Mishkat; Iqbal, Sheeraz (International journal of electrical power & energy systems, 2021)
•Parallel PV/BSSs are integrated with the grid using a VSG control.•The VSG control is utilizing an ADC for the system frequency regulation.•GA optimization is used to find the optimized values for VSG control parameters.•Three different case studies including an IEEE 14 bus system is utilized. The future power system is developing to an inverter-based system from a machine dominated power system due to a large integration of renewable energy sources (RESs). Lack of inertial part and intermittency of the RESs causes frequency instability in the power system. The virtual synchronous generator (VSG) development has been made to add inertial control to the power system for controlling the frequency deviation caused by the integration of the photovoltaic system. The VSG system comprised of power electronics components having a droop control mechanism like the conventional synchronous generator, which provides the necessary frequency stability to the power system. In this paper, three parallel VSG based photovoltaic systems integrated with battery storage systems are used to analyze the frequency response and its stability. Moreover, an advanced genetic algorithm optimization method is used to get the optimal values of parameters of the droop controller used in VSG. Furthermore, two different cases with respect to variation in supply and load power of the system are analyzed in detail. Additionally, an IEEE 14 bus system is utilized to validate the proposed system in MATLAB/Simulink. Evident improvements are observed in the simulation results presented through the suggested GA based VSG control technique.